СІМЕЙНИЙ НЕМЕДУЛЯРНИЙ РАК ЩИТОПОДІБНОЇ ЗАЛОЗИ - Guda, B.B.; Komisarenko, I.I.; Ostafiichuk, M.V.; Tronko, M.D. (PH Akademperiodyka, 2023)
Background:Familial non-medullary thyroid carcinoma (FNMTC) is defined as cancer developing in two or more first-degree relatives if predisposing factors, for example, radiation, are absent. The disease can be either syndromic, when it is a component of complex genetic syndromes, or non-syndromic (95% cases). The genetic basis of non-syndromic FNMTC is unknown; the clinical behavior of tumorsis unclear and, at times, contradictory.Aim: To analyze clinical manifestations of FNMTC and compare them with the data for sporadic papillary thyroid carcinomas in patients of the same age groups. Materials and Methods:We examined 22 patients (a “parents” group and a “children” group) suffering from the non-syndromic FNMTC. For comparison, two groups of sporadic papillary carcinomas patients of the same age were drawn up(“adult” and “young”). We analyzed tumor size and frequency of the distributionby the categoryof TNM system, invasiveness, multifocality, metastases to lymph nodes, type and extent of surgical and radioiodine treatment, and prognosis according to the MACIS criterion. Results:Whether sporadic or familial, the tumor size, metastatic potential, and invasive potential are higher in young people, asalready known. There was no significant difference between the “parents” and “adult” groups of patients in terms of tumor parameters. One exception was the higher frequency of multifocal tumors in the FNMTC patients. Meanwhile, compared to the “young” sporadic papillary carcinomas patients, the FNMTC “children” had a higher frequency of T2 tumors, metastasizing (N1a–N1ab), and multifocal tumors, but a lower frequency of carcinomas with intrathyroidal invasions.In the FNMTC “children” compared to FNMTC “parents” was a higher frequency of T2 tumors, metastasizing carcinomas, and tumors with capsular invasion. Conclusion:FNMTC carcinomas are more aggressive than sporadic ones, especially in patients who are first-degree relatives in a family with parents already diagnosed with the disease.